A Scrum-based framework for new product development in the non-software industry - Cano, Emilio L; García-Camús, Juan M.; Garzás, Javier; Moguerza, Javier M.; Sánchez, Noemí N. (Elsevier B.V., 2022)
Scrum is an iterative and incremental development framework that, nowadays, is mainly used for software development. In this work, a Scrum-Based New Product Development (SBNPD) approach is introduced. This new framework stems from the basis of Scrum and incorporates tools suitable for being applied to the design and development of physical products. The proposed approach implies that feedback from early adopters is to be gathered throughout the whole project, thereby driving to validated learning within a co-creation process. A case study illustrates how the SBNPD framework is applied for the development of a physical product within the dental industry.
Keywords: agile project management; framework; innovation strategy; Scopus; JCR